Double‐Network Heparin Dynamic Hydrogels: Dynagels as Anti‐bacterial 3D Cell Culture Scaffolds. Issue 24 (12th April 2021) - Cui, Han; Wang, Qimeng; Zhang, Ye; Barboiu, Mihail; Zhang, Yan; Chen, Jinghua
Abstract: Double cross‐linked dynamic hydrogels, dynagels, have been prepared through reversible imine bonds and supramolecular interactions, which showed good pH responsiveness, injectability, self‐healing property and biocompatibility. With the further encapsulation of heparin, the obtained hydrogels exhibited good anti‐bacterial activity and promotion effects for 3D cell culture. Abstract : Multicomponent dynagels for heparin encapsulation : Dynamic covalently cross‐linked dynamers with high mechanical strength, biocompatibility and self‐healing behaviors have been used for biomedical applications.